Literature Review: Massage effleurage Terhadap Respon Nyeri Pada Ibu Bersalin Kala I Fase Aktif - Nining Sulistyowati (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2021)
AbstractMost of the maternity mothers stated that they could not stand the pain they felt, especially in the abdomen, waist, back and radiating to the spine, so that the mother continued to feel pain during the first stage of labor. Contractions during labor can cause pain. Labor pain is a problem that has not received special attention, even though the purpose of intrapartum care itself is to reduce pain in labor, in addition to providing calm and comfort to the mother, it can also help speed up the process of opening the birth canal. reduced by taking non-pharmacological actions, one of which is the provision of massage effleurage. Massage effleurage which is done in the abdominal area to help reduce pain that arises during the labor process. The purpose of this study was to determine whether massage effleurage can reduce the pain response in women in the first stage of labor based on the literature review. The design of scientific papers is in the form of a literature review with three articles taken from the Google Scholar journal page with the keyword